P 84 Altered sensorimotor integration of afferent inhibition in patients with complex regional pain syndrome. (May 2022) - Drämel, N.; Thoma, P.; Fleischmann, R.; Grothe, M.; Lotze, M.; Strauss, S.
Abstract : Introduction: The complex regional pain syndrome (CRPS) is a chronic pain condition which frequently results in sensorimotor dysfunction of the affected limb. With respect to pathophysiology an impaired interaction in sensorimotor cortex has been hypothesized 1 . Sensorimotor interactions can be assessed through transcranial magnetic stimulation (TMS) that is preceded by an electrical stimulation of peripheral motor or sensory nerves (short/ long afferent inhibition; SAI/LAI). Previous studies revealed only minor alterations of LAI using peripheral motor stimulation in CRPS 2 . This study uses a more comprehensive assessment of SAI and LAI, induced by motor and sensory peripheral stimulation, to assess interaction of the sensorimotor system in CRPS. Methods : 13 unilateral upper limb affected patients with CRPS (9 females, 54 ± 17.8 years) and 11 controls (HCs; 8 females, 52± 18.3 years) received TMS on either hemisphere. SAI and LAI were induced by a motor (m_) or sensory (s_) median nerve stimulation preceded by TMS with 20ms (m_SAI) and 200ms (m_LAI) or 23ms (s_SAI) and 203ms (s_LAI), respectively 3 . Twenty paired and single TMS stimuli were randomly applied for each condition. Results: Pain levels were 5.1±1.5/10 at rest and 7.4±2.1/10 during movements. ANOVA revealed a significant group effect for patients vs. HCs on the affected side (F=2.2, p=0.048). Post hoc tests were corrected for multiple comparisons and showed reduced inhibition in patients after sensory stimulation (s_SAI: t=-2.51, p=0.04; s_LAI: t=-2.53 p=0.038) and motor stimulation with ISI 200ms (m_LAI: t=-2.62, p=0.032). Afferent sensorimotor inhibition was lower in patients with longer disease duration (r=-0.66, p=0.014). Discussion: We demonstrate altered sensorimotor integration of afferent inhibition in CRPS. Since afferent inhibition after sensory stimulation is thought to be mediated via interconnections especially between Brodmann area 3b of somatosensory and the motor cortex, our results complement existing literature about maladaptive cortical plasticity of these regions in CRPS 4, 5 . Impairment in LAI, that is thought to involve higher-order somatosensory cortical areas and the posterior parietal cortex is in line with existing literature on chronic pain 2, 4 . Future longitudinal investigation should evaluate intra- and intercortical sensorimotor integration systematically in CRPS to better understand their impact in development of sensorimotor symptoms. Literature: 1 Harris AJ. Cortical origins of pathological pain. Lancet 1999. 2 Morgante et al. Normal sensorimotor plasticity in complex regional pain syndrome with fixed posture of the hand. Mov Disord. 2017. 3 Sailer A, et al. Brain. 2003. 4 Chen et al. Modulation of motor cortex excitability by median nerve and digit stimulation. Exp Brain Res. 1999. 5 Pfannmöller et al. Investigations on maladaptive plasticity in the sensorimotor cortex of unilateral upper limb CRPS I patients. RNN. 2019.